2019
DOI: 10.1097/bsd.0000000000000908
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of an Intraoperative Povidone-Iodine Irrigation Protocol in Spinal Surgery for Surgical Site Infection Prevention

Abstract: Study Design: This was a retrospective observational study. Objective: The aim of this study was to evaluate the efficacy of our new protocol for preventing postoperative surgical site infection (SSI) following spinal surgery. Summary of Background Data: SSI following spinal surgery is a serious postoperative complication. Several studies have recently assessed the effectiveness of wound irrigation with povi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 32 publications
0
16
0
1
Order By: Relevance
“…Many studies have been conducted on wound irrigation during different types of surgery. For example, Onishi et al ( 22 ) showed that using saline wound irrigation and PI intraoperatively was associated with a reduced incidence of SSI following spinal surgery. Another study showed that using chlorhexidine gluconate wound irrigation when antibiotics were not given within 60 min pre-operatively was associated with a reduced incidence of SSI following cesarean section ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have been conducted on wound irrigation during different types of surgery. For example, Onishi et al ( 22 ) showed that using saline wound irrigation and PI intraoperatively was associated with a reduced incidence of SSI following spinal surgery. Another study showed that using chlorhexidine gluconate wound irrigation when antibiotics were not given within 60 min pre-operatively was associated with a reduced incidence of SSI following cesarean section ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, 90 sec of 1% PVP-I pooling every 1.5 h followed by saline irrigation has been suggested to be safe for the prevention of postoperative deep SSI after spinal surgery. 14…”
Section: Discussionmentioning
confidence: 99%
“…There is limited data on the safety dose spectrum of PVI for spinal surgeries. [12][13][14] On the other hand, normal saline has the lowest toxicity, but it only dilutes and does not cleanse the contaminants. 13 We conducted the current randomized clinical trial aimed to evaluate the effect of wound irrigation with PVI and normal saline on infection rate, wound healing, fusion status and clinical outcomes of spinal surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Chlorhexidine irrigation in caesarean section did not signi cantly decrease SSI [16]. During spinal surgery, deep SSI was signi cantly reduced after surgery when irrigation was performed with PI at regular intervals during surgery [7]. Topical antibiotics are also applied to the surgical wound to reduce SSI.…”
Section: Discussionmentioning
confidence: 99%
“…To decrease the SSI rate, wound irrigation utilizing various materials are performed. Povidone-iodine (PI) irrigation during spinal surgery signi cantly reduced the SSI rate compared to saline irrigation [7]. In abdominal surgery, subcutaneous wound irrigation with 0.04% polyhexanide solution signi cantly reduced SSI [8].…”
Section: Introductionmentioning
confidence: 99%